Redox-active ligand controlled selectivity of vanadium oxidation on Au(100). Issue 6 (12th January 2018) - Tempas, Christopher D.; Morris, Tobias W.; Wisman, David L.; Le, Duy; Din, Naseem U.; Williams, Christopher G.; Wang, Miao; Polezhaev, Alexander V.; Rahman, Talat S.; Caulton, Kenneth G.; Tait, Steven L.
Abstract : Selective oxidation of V is observed when coordinated with a redox-active ligand, forming a single VO product. Abstract : Metal–organic coordination networks at surfaces, formed by on-surface redox assembly, are of interest for designing specific and selective chemical function at surfaces for heterogeneous catalysts and other applications. The chemical reactivity of single-site transition metals in on-surface coordination networks, which is essential to these applications, has not previously been fully characterized. Here, we demonstrate with a surface-supported, single-site V system that not only are these sites active toward dioxygen activation, but the products of that reaction show much higher selectivity than traditional vanadium nanoparticles, leading to only one V-oxo product. We have studied the chemical reactivity of one-dimensional metal–organic vanadium – 3, 6-di(2-pyridyl)-1, 2, 4, 5-tetrazine (DPTZ) chains with O2 . The electron-rich chains self-assemble through an on-surface redox process on the Au(100) surface and are characterized by X-ray photoelectron spectroscopy, scanning tunneling microscopy, high-resolution electron energy loss spectroscopy, and density functional theory. Reaction of V-DPTZ chains with O2 causes an increase in V oxidation state from V II to V IV, resulting in a single strongly bonded (DPTZ 2− )V IV O product and spillover of O to the Au surface. DFT calculations confirm these products and also suggest new candidate intermediate states, providing mechanistic insight into this on-surface reaction. In contrast, the oxidation of ligand-free V is less complete and results in multiple oxygen-bound products. This demonstrates the high chemical selectivity of single-site metal centers in metal–ligand complexes at surfaces compared to metal nanoislands.